STRATEGI DINAS KOPERASI DAN UMKM DALAM PEMBERDAYAAN EKONOMI MASYARAKAT (Studi pada Kerajinan Marmer Dan Onix di Kecamatan Besole Kabupaten Tulungagung) - ANTON PRIYO WICAKSONO (Universitas Negeri Surabaya, 2014)
Craft marmer and onix as potential areas to be developed require the participation of government agencies Tulungagung through relevant in this case the Department of Cooperatives and UMKM as outreach efforts to keep small and medium businesses run by people both individually and self-maintained and grown and able to continue to grow into a competitive industry that can compete with big businesses. The method used is descriptive qualitative research locations in the office of Department of Cooperatives and UMKM Tulungagung and some industrial centers Onix stone and Marmer handicrafts in the village of Besuki , District Campurdarat . In order to improve the welfare of the community, in accordance with the provisions of the State Minister of Cooperatives and UMKM with the Guidelines and PROPERNAS foundation, strategies implemented Cooperatives and UMKM , among others , first by growing a healthy business climate conducive to the development of UMKM by way of appeal to businesses to compete be healthy and work together, improve coordination across stakeholders such as the development of UMKM to easily and simplification of bureaucracy in the process of licensing to marketing and export production, the Government also has a soft loan program that can be used to increase capital community. Second, increased access to productive resources through infrastructure improvements and additions, facilities and infrastructure, improving the quality of human resources through sharing , training and seminars and business consulting services for free. Third, the development of entrepreneurship and UMKM superior competitive by improving the quality of human resources , utilization of local resources to the maximum and to formulate their programs so that the resulting product competitiveness. It can be concluded that the Department of Cooperatives and UMKM Tulungagung district has three principal strategies as community empowerment, so that people can be independent and able to take advantage of the potential that exists in their area into a product that has the competitiveness and enhancing the ability of the community 's economy. Keywords : Strategy, Department of Cooperatives and UMKM, Economic Empowerment.